Populism, “Anti” Ideologies, and Feminist Coalitions - Ackerly, Brooke A. (Frontiers in Sociology, 2021)
By understanding populism as an “anti-” politics we can see two strands of populism: the anti-democratic strand which marginalizes certain groups of people and the anti-structural injustice strand coming from marginalized people. The potential of this anti-structural injustice activism encourages activists to expand their coalitional politics and government and philanthropic donors to see the import of funding and otherwise supporting work against structural injustice that explicitly takes on patriarchy and racism, among the full gamut of ideologies based on hierarchy and injustice.